Manuel II Palaiologos, 1350-1425 - Çelik, Siren, 1989- (New York)
xxiii, sayfa, [2] sayfa harita, 445 sayfa
Keywords: “Few Byzantine emperors had a life as rich and as turbulent as Manuel II Palaiologos. A fascinating figure at the crossroads of Byzantine, Western European and Ottoman history, he endured political turmoil, witnessed no less than three sieges by the Ottomans and travelled as far as France and England. He was a prolific writer, producing a vast corpus of literary, theological and philosophical works. Yet, despite his talent, Manuel has largely been ignored as an author. This biography constructs an in-depth picture of him of as a ruler, author and personality, as well as providing insight into his world and times. It offers the first analysis of the emperor's complete oeuvre, focusing on his literary style, self-representation philosophical/theological thought. By focusing not only on political events, but also on the personality, personal life and literary output of Manuel, this biography paints a new portrait of a multifaceted emperor“ --